Sub-sea gas processing - Parks, David William (Curtin University, 2011)
To meet the demands of deeper and more remote reservoirs, subsea processing has been poised as one of the most potentially promising technology developments in the offshore development.Natural Gas usually contains significant quantities of water vapour, which must be removed for gas processing and transmission. A pipeline transporting natural gas at a pressure of 10 Mega Pascals at equilibrium with seawater at 4 C must have water content lower than around 144 parts per million (by volume) to ensure water will not condense within the pipeline. Failure to sufficiently reduce the water content can lead to condensation of liquid water and the formation and accumulation of gas hydrates into pipe blocking plugs. This is particularly important for subsea pipelines with the high pressure and low temperatures conditions that exposes the gas to hydrate formation conditions.This research investigates a novel dehydration solution that is applicable for subsea installation. The technique is based on technology that was trialled in an above ground implementation by Cool Energy with significant system modifications to make it applicable to a subsea environment. The ultimate objective of this research is to develop a sea bed dehydration solution that will reduce the water content of the gas to pipeline quality standard.The solution utilises the concepts of gas cooling through expansion and the controlled formation and management of gas hydrates to reduce the water content of a saturated gas stream to levels suitable for gas transport in subsea pipelines. A pilot plant was implemented to test the solution design at pressures up to 10 Mega Pascals and flow rates of 35 standard cubic meters per hour. The experiments successfully demonstrated gas dehydration to below -40 degrees C, performance that meets the pipeline water specification requirements for subsea transportation of natural gas.This thesis presents the current status of implemented subsea technology, reviews current dehydration technologies and discusses their applicability to subsea implementation. It describes the iterative dehydration process development and presents the achieved dehydration results. A production scenario is defined and a modelled solution presented together with novel approaches in management of the system.